Bark Extracts of Chamaecyparis obtusa (Siebold & Zucc.) Endl. Attenuate LPS-Induced Inflammatory Responses in RAW264.7 Macrophages - Bo-Ae Kim; Ji-A Byeon; Young-Ah Jang; Yong-Jin Kwon (Plants)
Chamaecyparis obtusa (Siebold & Zucc.) Endl. (C. obtusa) is an evergreen conifer native to temperate regions such as South Korea and Japan, traditionally used for its anti-inflammatory properties. However, the molecular mechanisms underlying the anti-inflammatory effects of C. obtusa bark extracts remain poorly understood. In this study, I compared the biological activities of C. obtusa bark extracts prepared using boiling water (COWB) and 70% ethanol (COEB), and investigated their anti-inflammatory mechanisms in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. COEB significantly suppressed both mRNA and protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), along with decreased production of their respective inflammatory mediators, nitric oxide (NO) and prostaglandin E2 (PGE2). Additionally, COEB selectively downregulated interleukin (IL)-1β expression, without affecting tumor necrosis factor-α (TNF-α), and unexpectedly upregulated IL-6. Notably, COEB did not inhibit the LPS-induced activation of major inflammatory signaling pathways, including mitogen-activated protein kinase (MAPK), nuclear factor-kappa B (NF-κB), and Janus kinase/signal transducer and activator of transcription (JAK/STAT). These findings suggest that COEB exerts anti-inflammatory effects by modulating key inflammatory mediators independently of canonical signaling pathways and may offer a novel therapeutic strategy for controlling inflammation.